Trend of Value-added Assessment of Nudge Adolescent Mental Health from the Perspective of AI - Zhiwen Tang, Ying Lin, Hailong Sun, Rongjun Zhao, Fang Bian (Forest Chemicals Review)
Intelligent wearable devices, APP and mini programs of mobile phone are increasingly widely used, providing more objective and dynamic data for adolescent mental health monitoring. The development of artificial intelligence promotes the diversity of adolescent mental health evaluation and intervention. Because the factors affecting mental health of adolescents are complicated by individual personality traits, peer relationship and family, it is necessary to explore the relationship between different factors based on the viewpoint of value-added assessment, and to dig out the key intervention problems and influencing factors. From the perspective of artificial intelligence equipment and value-added assessment, a multi-level value-added assessment system of individual, family, school and community is constructed to form an organic value-added system of mental health so as to promote the mental health of adolescents individually.